The Influence of the Basic Features of a User on the Application of Information Systems - Šadić, Sead; Puška, Adis; Beganović, Admir I.; Berbić, Selma (Oeconomica Jadertina, 2017)
When exploring the relationship between users and information systems, it is necessary to ascertain what impact the user's basic features have on their experience of the information systems they use in their work. Accordingly, this survey was conducted in the Government of Brčko within the district of Bosnia and Herzegovina, and within the Public company Brčko Municipality. The survey was conducted on 479 employees, while 261 employees completed the questionnaire developed for this research. When measuring the basic characteristics of the respondent’s gender was considered, as well as the work place, age, qualifications, their work experience and the amount of use of the information system weekly. When measuring the experience of using the information system, a modified model of performance of the information system was used. The SPSS 20.0 statistical software tool was applied during the testing of the proposed hypothesis, and the multivariate variance analysis (MANOVA) and the variance analysis (ANOVA) were used for the analysis. A factor analysis was used with the grouping of the proposed claims. The results obtained using this analysis show that in the modified model of success of the information system the statements were grouped into 4 factors. The hypothesis test results have shown that there is a significant statistical dependence on the use of information systems in almost all features of a user, except for the age of users where there is no statistical dependence. The results obtained from this research will contribute to a better understanding of how users experience information systems in their work and what basic features of the respondents affect the use of the system.
Keywords: modified model of success of information systems; basic user features; multivariate variance analysis; factor analysis